Determinant Factors in Managing Tourism Village: A Destination Attributes Approach - Herman Herman; Putri Rizkiyah; Herry Rachmat Widjaja; Ilham Junaid (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2023)
Studies on destination attributes mainly focused on the motivation or experience of tourists and their relation to these attributes. Therefore, in-depth reports are required to fully understand tourism villages as destinations, particularly in relation to the factors that contribute to their success. This study aimed to (1) identify tourism products in tourism villages, (2) identify the determinants of tourism destination attributes, and (3) recommend efforts to improve the management of destination attributes in developing as tourism villages. A qualitative approach was used which was conducted at Kuta Village, Lombok, in 2022. The results showed the tourism products in Kuta Village are the local population's natural landscape, culture, and hospitality. The determining factors that support the management of destination products were strategic locations, various tourist attractions and activities, availability of amenities, as well as good accessibility. However, the village managers needed to address essential issues, such as parking facilities, transportation, and limited skilled personnel in providing services to tourists. This study recommended three steps for managing destination attributes, namely training in sustainable home stay management, improving tourism-supporting facilities and infrastructure, as well as regulating physical infrastructure and accessibility. Moreover, there were arguments (insights) regarding the existence of a village as a destination with the management of attributes and determinants. These served as the key to the successful management of tourism destination.